The theory and management of tropical multispecies stocks a review with emphasis on the Southeast Asian demersal fisheries. - Pauly, Daniel (Manila, Philippines ICLARM, 1983)
ICLARM Contribution No.19
Keywords: Fishery management; Fish populations; Fisheries; Fishery management